A comparative study of the influence of three pure titanium plates with different micro‐ and nanotopographic surfaces on preosteoblast behaviors. Issue 11 (29th April 2013) - Zuo, Jun; Huang, Xunzhi; Zhong, Xiaoxia; Zhu, Bangshang; Sun, Qiang; Jin, Chengyu; Quan, Hongzhi; Tang, Zhangui; Chen, Wantao
<x xml:space="preserve">Abstract</x> There is a great demand for dental implants with the ability to accelerate periimplant bone regeneration. Modification of surface micro‐ and nanotopographies has been revealed to affect bone cell metabolism. In this study, we utilized dielectric barrier discharge (DBD) technology to modify commercially pure titanium (Ti‐tr) surfaces and then investigated the cytocompability of DBD‐modified Ti surface when compared with machined (Ti‐m) and polished (Ti‐p) Ti surfaces. These three kinds of Ti plates exhibited different surface energies and topographies at the micro‐ and nanoscale levels. The DBD‐treated pure Ti surface significantly enhances cell adhesion, spread, and proliferation of MC3T3‐E1 preosteoblast cells compared with the Ti‐p and Ti‐m surfaces, suggesting that Ti‐tr has better cytocompatibility compared with the other two surfaces. Preosteoblast cells on Ti‐m surface exhibited higher alkaline phosphatase activity than cells on Ti‐tr and Ti‐p surfaces 14 days after seeding. No significant difference in alkaline phosphatase activity was observed between cells grown on Ti‐tr and Ti‐p surfaces. Our study demonstrated that DBD modification significantly enhanced cell adhesion, spread, and proliferation of preosteoblasts with no negative effects on cell differentiation. Microtopography and nanotopography of the surfaces of different materials and chemical/energetic properties have a synergistic effect on cell attachment, proliferation, and differentiation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3278–3284, 2013.